Forward guidance and "lower for longer": The case of the ECB - Tilman Bletzinger; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2016)
A number of contributions to research on monetary policy have suggested that policy should be asymmetric near the lower bound on nominal interest rates. As inflation and economic activity decline, policy should ease more aggressively than it would in the absence of the lower bound. As activity recovers and inflation picks up, the central bank should act to keep interest rates lower for longer than without the bound. In this note, we investigate to what extent the policy easing implemented by the ECB since summer 2013 mirrors the rate recommendations of a simple policy rule or deviates from it in a way that indicates a 'lower for longer' approach to policy near zero interest rates.
urn:nbn:de:hebis:30:3-395780
Keywords: E43; E47; E52; E58; 330; monetary policy; interest rates; European Central Bank; forward guidance; zero lower bound